Syntheses And Antibacterial Screening Of Juglone Derivatives - Tan , Daniel Teoh Chuan (2010)
The juglone natural product has been used as the starting material in the syntheses of various bioactive quinones like ochromycinone. The present study involves the syntheses of juglone derivatives from both juglone and non-juglone starting materials. The ochromycinone precursor, 1,2,3,4-tetrahydro-8-hydroxy-3-methylbenz[a] anthracene-7,12-dione (19) was synthesised from juglone in two steps. The first step was the Diels-Alder reaction and the second step was the aromatisation reaction. In addition, a new para-nitrojuglone derivative (51) was obtained as the sole isomeric product from the direct nitration of juglone.